Імуноцитохімічне (HBME-1, ТПО) та цитохімічне (ДАП IV) дослідження після ТАПБ вузлів щитоподібної залози - Хоперія, В. Г. (Clinical Endocrinology and Endocrine Surgery, 2010)
It was reported previously that more precise diagnosis of thyroid cancer could be achieved if, in addition to cytological diagnosis on FNA smears, reliable markers for thyroid malignancy were used. A recent immunohistochemistry study was demonstrated that the antigen recognized by HBME-1 has a stronger expression in malignant than benign thyroid tumors in both surgical and FNA cell blocks. The present study is aimed not only to validate the role of HBME-1, but rather to establish the combination of the thyroid peroxidase immunocytochemistry with MoAb 47, HBME-1 and DAP IV staining on FNA specimens of thyroid nodule. The analysis was performed on FNA samples from 111 thyroid tumors: The diagnostic sensitivity of TPO staining was 100%, its specificity 92,8%. The sensitivity of DAP IV staining was less for diagnosis of malignancy was 69,2%, its specificity 91,5%. Despite of overall sensitivity 98% of HBME-1, it was only 44% specific. HBME-1 is a sensitive marker of thyroid carcinoma. However, using of TPO immunostaining and detection of DAP IV activity can be increases the level of sensitivity of thyroid cytology without decreasing its specificity.